2010
DOI: 10.1042/an20090048
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia and Diabetes Impair Gap Junctional Communication among Astrocytes

Abstract: Sensory and cognitive impairments have been documented in diabetic humans and animals, but the pathophysiology of diabetes in the central nervous system is poorly understood. Because a high glucose level disrupts gap junctional communication in various cell types and astrocytes are extensively coupled by gap junctions to form large syncytia, the influence of experimental diabetes on gap junction channel-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 108 publications
1
103
0
1
Order By: Relevance
“…37 This study extends these In this study, increasing BP in SCI only partially improved the NVC-PCA response; however, suggesting other CBF regulatory mechanisms may be dysfunctional in SCI. Attenuated NVC, even after midodrine, could be due to a variety of factors outside of low BP, including reduced nitric oxide availability, 38 glucose intolerance, 39 and dyslipidemia. 40 This study clearly showed that NVC of the MCA is preserved to AB levels in those with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…37 This study extends these In this study, increasing BP in SCI only partially improved the NVC-PCA response; however, suggesting other CBF regulatory mechanisms may be dysfunctional in SCI. Attenuated NVC, even after midodrine, could be due to a variety of factors outside of low BP, including reduced nitric oxide availability, 38 glucose intolerance, 39 and dyslipidemia. 40 This study clearly showed that NVC of the MCA is preserved to AB levels in those with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Gap junction-coupled astrocytes can avidly take up lactate from extracellular fluid and are poised to discharge it from their endfeet into perivascular fluid where pulsatile pressure can drive the lactate along the vasculature (Gandhi et al (2009);Ball et al (2007Ball et al ( , 2010 and cited references). Several studies have reported that lactate increases vasodilation by different mechanisms (Hein et al, 2006;Yamanishi et al, 2006;Gordon et al, 2008), and continuous lactate release from the activated brain may serve a signaling function to increase blood flow and fuel delivery to the brain.…”
Section: Lactate Can Stimulate Vasodilationmentioning
confidence: 99%
“…Brain growth and metabolic and functional development have enormous spurts between 10 and 21 days, with slower increases thereafter (Baquer et al, 1975 Yu et al (1984)), and cerebellar granule neurons obtained from B7-day-old postnatal rodents are used as a model system for glutamatergic neurons (Schousboe et al (1985); Hertz et al (1988) and cited references). Harvest age, culture duration, conditions, medium composition, and cellular development during culturing influence characteristics of cultures (Hertz et al (1998), Hertz (2004) and cited references), as well as any acquired pathophysiology during culturing (e.g., 15 to 30 mmol/L glucose causes diabetic complications; Gandhi et al (2010)). The capacity to use glucose or lactate by cultured astrocytes and neurons grown for < 2 weeks in vitro need not be equivalent to the adult brain.…”
Section: Properties and Physiology Of The Experimental Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…D-Glucose concentration in a culture medium for different types of cells might be different because of differences in their physiological state. To those like endothelial cells, macrophages, and astrocytes, 5 mM D-glucose might be appropriate (Huawei et al 2013;Kaplan et al 2010;Gandhi et al 2010). However, to other cells such as cortical or hippocampal neurons, optimal survival rate and neurite growth may require much higher basal Dglucose (e.g., 25 mM), reflecting the fact that neurons have high metabolic rates.…”
mentioning
confidence: 99%